Anticancer Activity of Sunflower (Helianthus annuns L.) Seeds oil against cell lines - Al-Jumaily, Rakad; Al-Shamma, Nawal; Al-Halbosiy, Mohammed; Al-Shamma, Laith (Iraqi Journal of Science, 2024)
This study investigated the role of sunflower (Helianthus annuns L.) seed extracts as a cytotoxic agent against two cell lines (RD and L20B) using different concentrations of sunflower seeds oil 1.3 , 2.6 , 5.2, 10.4 , 20.8, 41.6 , 83.2 and 166.4 μg / ml for different exposure time (24 ,48 and 72 hrs). The results revealed a clear cytotxoic activity of sunflower seeds oil on growth of RD cancer cell line, and the effect was concentration-dependent.The signification inhibition (P<0.05) was obtained at a concentration of 83.5 and 166.4 μg / ml as compared to control. In addition, the growth of RD cell line was more sensitive to sunflower seeds oil in comparison with the growth of L20B transform cell line. In conclusion, the extract showed inhibitory effect on cancer cell line and it is promising to use as anticancer drug.